An in vitro study of the defluoridating capacity of apog with concentrations of 0.1 - 0.5 grams on artificially fluoridated water - Cabarrubia, Czarina
The defluoridating capacity of apog with concentrations of 0.1-0.5 gms for a constant volume of artificially fluoridated water was studied. The results show that smaller apog quantities can defluoridate artifically fluoridated water. As the apog concentration was increased, the amount of fluoride removed was also increased. Tests in the PH Value of the water samples reveal that there is a change in PH after defluoridating artificially fluoridated water with apog.